Chasing Down the Eu2+ Ions: The Delicate Structure−Property Relationships in the Ultra‐Narrow Band Phosphor K1.6Na2.1Li0.3[Li3SiO4]4:Eu2+. Issue 24 (8th October 2021) - Ruegenberg, Freia; García‐Fuente, Amador; Seibald, Markus; Baumann, Dominik; Peschke, Simon; Urland, Werner; Meijerink, Andries; Huppertz, Hubert; Suta, Markus
Abstract: Eu 2+ ‐activated phosphors of the UCr4 C4 structure type have emerged as promising new (ultra‐)narrow band phosphors. Especially the UCr4 C4 ‐type alkali lithosilicates have caused a sensation in the field of phosphor research in the recent years due to their consistent (ultra)narrow‐band luminescence in the cyan and green range that can pave the way to novel backlighting LEDs with high color gamut. The compound "K2 Na2 [Li3 SiO4 ]4 :Eu 2+ " stands out with a strikingly narrow emission in the cyan range (<0.2 eV or <30 nm full width at half maximum in the energy or wavelength scale, respectively) but the position of the Eu 2+ ions within this structure has been so far controversial. High‐resolution photoluminescence spectroscopy at 10 K reveals a complex emission spectrum with seven emission bands in the violet to green range. Combination with single‐crystal X‐ray diffraction (SCXRD) demonstrates that the cation channels in the structure also contain Li + ions. The presence of emission bands in the violet and blue spectral range reveals that the Eu 2+ ions also occupy the available K sites in the structure independently confirmed by advanced ligand field calculations. This study demonstrates that a combination of SCXRD, photoluminescence spectroscopy, and theory can help elucidate advanced structural problems. Abstract : The combination of high‐resolution photoluminescence spectroscopy and X‐ray diffraction analysis on a single crystal with the molecular formula K1.6 Na2.1 Li0.3 [Li3 SiO4 ]4 :Eu 2+ offers new insights into structure−property relationships. Together with advanced ligand field calculations, this approach helps elucidate the different positions of the Eu 2+ ions in a complex structure with aid of luminescence spectroscopy.